Kinerja dosen ditinjau dari berbagi pengetahuan tacit dan komitmen organisasi - Raja Raya Saragih; Rita Retnowati; Dian Wulandari (Lentera Negeri, 2026)
To gain a deep understanding of the effectiveness of lecturer performance, an exploratory study was conducted by identifying five main variables that are considered to have a key role in improving lecturer performance, namely sharing tacit knowledge, organizational climate, organizational commitment and innovative behavior. The five variables were then tested quantitatively to build a lecturer performance model that is relevant to the dynamics of higher education and formulate more effective and sustainable strategies. This quantitative study involved 230 permanent lecturers at private universities in the Bekasi and Banten areas. Data collection was carried out through distributing questionnaires using the Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis technique. The results of this study demonstrate that the lecturer performance model built has met the Goodness of fit criteria. The results of the hypothesis test confirm that tacit knowledge sharing, organizational climate, organizational commitment and innovative behavior have a significant positive effect on lecturer performance. While tacit knowledge sharing and organizational climate have a positive effect on organizational commitment. Furthermore, tacit knowledge sharing and organizational climate have a significant positive effect on innovative behavior. SITOREM analysis confirmed that improving lecturer performance can be done through strengthening the indicators of tacit knowledge sharing, organizational climate, organizational commitment, and innovative behavior that are already good, as well as updating indicators that are still lacking.